2010
DOI: 10.1007/s00415-010-5653-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term functional outcomes and psychological sequelae in Guillain–Barre syndrome

Abstract: GBS is complex and requires long-term management of psychological sequelae impacting activity and participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 33 publications
3
39
1
Order By: Relevance
“…In a similar study [12] among 70 patients examined 3-5 years after GBS, 27% reported changes in personal life style because of increased fatigability. Dornonville et al [3] and Khan et al [13] evaluated patients a mean of 6 years following the acute disease (range 1-14 years). In spite of good recovery of objective measures of motor skills, the quality of life of the patients showed prominent impairment as compared with healthy individuals in items related to capabilities at workplace and maintenance of social relationships, as well as in self-confidence and ability to live independently.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study [12] among 70 patients examined 3-5 years after GBS, 27% reported changes in personal life style because of increased fatigability. Dornonville et al [3] and Khan et al [13] evaluated patients a mean of 6 years following the acute disease (range 1-14 years). In spite of good recovery of objective measures of motor skills, the quality of life of the patients showed prominent impairment as compared with healthy individuals in items related to capabilities at workplace and maintenance of social relationships, as well as in self-confidence and ability to live independently.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report similar prevalence (27.7%) of urinary dysfunction in pwGBS, including urinary retention (9.2%) 13. In a study of factors impacting longer-term health-related outcomes in pwGBS ( n =76), 17% reported ongoing bladder dysfunction (urgency, frequency or nocturia) 11. Few studies however, report on the mechanism of bladder dysfunction and/or urodynamic data in this population 13.…”
Section: Introductionmentioning
confidence: 86%
“…The distal motor weakness, autonomic disturbances and psychological issues are the key features of GBS. Although majority of GBS survivors (75%) have good motor outcomes (i.e., ability to walk independently),7 the impact of GBS on activities of daily living, work, social activities and health-related quality of life (QoL) is considerable at 2-6 years after onset and persists beyond this time 8-11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motor deprivation and loss of communication were the most important causes of anxiety. Khan et al 29 reported that depression, anxiety and stress are observed in about 20% of GBS patients a median 6 years after their discharge from neuro-ICU. Therefore, these two studies have assessed anxiety during the stay and after discharge from the ICU, respectively, whereas the present study has focused on anxiety at admission.…”
Section: Discussionmentioning
confidence: 99%